2016
DOI: 10.25077/jka.v5i3.587
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Derajat Merokok Berdasarkan Indeks Brinkman dengan Kadar Hemoglobin

Abstract: AbstrakSalah satu zat yang terdapat dalam asap rokok adalah karbon monoksida yang sangat mudah berikatan dengan hemoglobin, sehingga tubuh mengalami hipoksia dan berusaha meningkatkan kadar hemoglobin. Tujuan penelitian ini adalah untuk menentukan hubungan derajat merokok berdasarkan Indeks Brinkman dengan kadar hemoglobin. Desain penelitian ini adalah cross-sectional study yang dilakukan terhadap pendonor darah di Palang Merah Indonesia cabang Padang. Jumlah subjek sebanyak 65 orang yang diambil secara accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 0 publications
2
5
0
6
Order By: Relevance
“…Subjects who were categorized as mild smokers were the most respondents in this study (39.4%), then followed by moderate smokers in the second place (36.4%) and the last were heavy smokers, 24.2%). This is in accordance with research conducted by Amelia et al, 14 where it was found that the most subjects in her study were mild smokers (41.5%, n = 27), the second was moderate smokers (32.3%, n=21), and the last one was heavy smokers (26.2%, n = 17). This occurs because the respondents were taken from various age groups and it affects the length of smoking of the respondents which causes the degree of smoking to be almost even in each category.…”
Section: Gerd Percentage Based On Agesupporting
confidence: 93%
See 1 more Smart Citation
“…Subjects who were categorized as mild smokers were the most respondents in this study (39.4%), then followed by moderate smokers in the second place (36.4%) and the last were heavy smokers, 24.2%). This is in accordance with research conducted by Amelia et al, 14 where it was found that the most subjects in her study were mild smokers (41.5%, n = 27), the second was moderate smokers (32.3%, n=21), and the last one was heavy smokers (26.2%, n = 17). This occurs because the respondents were taken from various age groups and it affects the length of smoking of the respondents which causes the degree of smoking to be almost even in each category.…”
Section: Gerd Percentage Based On Agesupporting
confidence: 93%
“…If a person smokes for a long time and the number of cigarettes smoked is increasing, then his smoking degree will be heavier. 14 Nicotine is one of the substances found in cigarettes where nicotine has an addictive effect that can cause smokers to become dependent. The nicotine in cigarettes can activate the dopamine reward pathway in the brain that encourages a person to smoke continuously.…”
Section: Gerd Percentage Based On Agementioning
confidence: 99%
“…The Brinkman index is used to see the degree of severity of smoking by using formula of cigarettes smoked a day multiplied by the length of smoking in the year. There is a significant relationship between the degree of smoking and the severity of COPD (Amelia et al, 2016;Shamara, Fachri, 2014). In the group of respiratory disorders (Table 4), the results of this study were in accordance with the theory that the severity of smoking has a significant relationship with the severity of COPD disease, in this case, based on the value of lung function.…”
Section: Resultsmentioning
confidence: 99%
“…Sedangkan substansi toksik dalam bentuk zat kimia yang volatil seperti nitrosamin, formaldehid banyak terdapat dalam asap rokok. Zat-zat ini dapat memberikan efek toksiknya dengan mekanisme spesifik dan pada sel-sel atau unit-unit makromolekuler sel tertentu terutama pada sistem pernapasan (Amelia, Nasrul, & Basyar, 2016).…”
Section: Pengertian Rokokunclassified
“…Meskipun saat ini ada rokok modern (elektrik), namun tetap saja memiliki bahaya. dan risiko penyakit bagi orang terdekat (Amelia et al, 2016).…”
Section: Bahaya Merokokunclassified